Strategies to Modulate the Redifferentiation of Chondrocytes - Hu, Xiaoshen; Zhang, Weiyang; Li, Xiang; Zhong, Dongling; Li, Yuxi; Li, Juan; Jin, Rongjiang (Frontiers in Bioengineering and Biotechnology, 2021)
Because of the low self-healing capacity of articular cartilage, cartilage injuries and degenerations triggered by various diseases are almost irreversible. Previous studies have suggested that human chondrocytes cultured in vitro tend to dedifferentiate during the cell-amplification phase and lose the physiological properties and functions of the cartilage itself, which is currently a critical limitation in the cultivation of cartilage for tissue engineering. Recently, numerous studies have focused on the modulation of chondrocyte redifferentiation. Researchers discovered the effect of various conditions (extracellular environment, cell sources, growth factors and redifferentiation inducers, and gene silencing and overexpression) on the redifferentiation of chondrocytes during the in vitro expansion of cells, and obtained cartilage tissue cultured in vitro that exhibited physiological characteristics and functions that were similar to those of human cartilage tissue. Encouragingly, several studies reported positive results regarding the modulation of the redifferentiation of chondrocytes in specific conditions. Here, the various factors and conditions that modulate the redifferentiation of chondrocytes, as well as their limitations and potential applications and challenges are reviewed. We expect to inspire research in the field of cartilage repair toward the future treatment of arthropathy.